Covid-19 Vaccine Act According to World Health Experts and Institutes - Irma Rachmawati Maruf; Sardjana Orba Manullang; Hotmaria Hertawaty Sijabat; Sitti Asnaeni. Am; Ali Pirdaus (Budapest International Research and Critics University, 2022)
This paper aims to obtain authentic scientific evidence about the status of the Covid-19 vaccination regulations from experts from both world health organizations and various institutions concerned with vaccination and pandemic issues. We obtained data to support this study from an electronic search for national and international health journals that focus on vaccination and preventing conflict in future meetings. We conducted in-depth studies and tests to turn off the data that we found answered the problem of this study wholly and validly. This study obtains secondary data from the evidence of previous scientific studies with a phenomenological approach, namely the exploration of accurate and accurate data to obtain valid answers. Based on the evidence and discussion of this data exposure, we can conclude that the vaccination law is a recommendation from the government to provide services against various threats caused by this pandemic, which is a recommendation that must be submitted persuasively and accurately. Thus, these findings become supporting data for further studies in the future.